The existence of fractional (g, f)-factors in networks - Sun, Zhiren,; Zhou, Sizhong, (Utilitas Mathematica, 2020)
In this paper, we investigate the existence of fractional (g, f)-factors with inclusion and exclusion properties, and present a degree condition for graphs to have fractional (g, f)-factors with inclusion and exclusion properties. Furthermore, it is shown that the degree condition in the main result is sharp in some sense. © 2020 Utilitas Mathematica Publishing Inc.. All rights reserved.